2019
DOI: 10.21203/rs.2.10472/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic Predictive Accuracy of Electrocardiographic Biomarkers of Sudden Cardiac Death within a Survival Framework: The Atherosclerosis Risk in Communities (ARIC) study

Abstract: Background—The risk of sudden cardiac death (SCD) is known to be dynamic. However, the accuracy of a dynamic SCD prediction is unknown. We aimed to measure the dynamic predictive accuracy of ECG biomarkers of SCD and competing non-sudden cardiac death (non-SCD). Methods—Atherosclerosis Risk In Community study participants with analyzable ECGs in sinus rhythm were included (n=15,716; 55% female, 73% white, age 54.2±5.8 y). ECGs of 5 follow-up visits were analyzed. Global electrical heterogeneity and traditiona… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

6
0

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…First, each beat on a 10-second 12-lead ECG recording was manually labeled by the team of physicians, as recently described. [14] Non-analyzable beats due to noise and artifacts, and non-dominant ectopic beats were excluded from analysis. Only normal sinus beats in a 10-second recording were included in the construction of a normal sinus median beat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, each beat on a 10-second 12-lead ECG recording was manually labeled by the team of physicians, as recently described. [14] Non-analyzable beats due to noise and artifacts, and non-dominant ectopic beats were excluded from analysis. Only normal sinus beats in a 10-second recording were included in the construction of a normal sinus median beat.…”
Section: Methodsmentioning
confidence: 99%
“…Equality of the areas under the (receiver operating characteristic, ROC) curve (AUC) for studied ECG and VCG predictors of SCD was compared using a Wald test of the null hypothesis that all classifier AUC values are equal. [22] In addition, as we recently showed that the best predictive accuracy of ECG biomarkers is within 2 years after ECG recording,[14] time-dependent (2-year) ROC AUC analysis was performed, using survival analysis framework[23, 24].…”
Section: Methodsmentioning
confidence: 99%
“…23 Both area and peak QRS-T angles were measured. 14,23,24 Quality control of automated ECG analysis was performed by investigators included median beat measurements (PR, QRS, QT intervals, and frontal P, QRS, and T axes), as well as durations, amplitudes, and areas of all identified by the algorithm waves and segments on all 12 leads. We used the results of automated 12-lead ECG measurements as reported by the 12SL algorithm, without further quality control procedures.…”
Section: Ecg and Vcg Analysismentioning
confidence: 99%
“…Global electrical heterogeneity (GEH) 13 is a novel vectorcardiographic (VCG) phenotype providing additional predictive value beyond traditional ECG metrics. 14…”
Section: Introductionmentioning
confidence: 99%
“…3 It integrates static and dynamic alternations in ventricular repolarization and conduction, which have been linked to ventricular arrhythmias in studies from the bench to the bedside. 6 Abnormal GEH is associated with SCD in the general population 3, 7 where it is explicitly associated with SCD over non-arrhythmic modes of death 3 , and an increased risk of drug-induced torsades-de-pointes. 8 The utility of assessing GEH for SCD risk stratification in CM patients with reduced LVEF who meet primary prevention ICD indications, however, is unknown.…”
Section: Introductionmentioning
confidence: 99%